2010
DOI: 10.4236/health.2010.21008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high fat food on erythrocyte phospholipids, fatty acids composition and glutathione redox-system of rats with alimentary dyslipidemia

Abstract: To evaluate the effects of high fat food consisted of tallow (19% of total diets) and cholesterol (2%) on modification of erythrocyte phospholipids, fatty acids composition and glutathione redoxsystem of male Wistar rats with alimentary dyslipidemia. The results demonstrated that after 30 and 180 days of high-fat feed erythrocyte phosphatidylinositol and phosphatidylcholine levels were reduced, phosphatidylserine were increased. Only on the 90 days of the experiment phosphatidylinositol level increased. In all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Reduction ratio 20:4 n6/20: 5n3 detected in 1group patients reflected the disturbance of FA synthesis - the forerunner of eicosanoics of the different series. This state of FA metabolism can lead to increased production of oksilipins 2nd and 4th series demonstrating vasoconstrictor, aggregation properties [1,28]. …”
Section: Resultsmentioning
confidence: 99%
“…Reduction ratio 20:4 n6/20: 5n3 detected in 1group patients reflected the disturbance of FA synthesis - the forerunner of eicosanoics of the different series. This state of FA metabolism can lead to increased production of oksilipins 2nd and 4th series demonstrating vasoconstrictor, aggregation properties [1,28]. …”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of this action is due to the fact that CBD exhibits much greater antioxidant activity (30–50%) than endogenous antioxidants, such as α-tocopherol or vitamin C [ 64 ]. In addition, GSH protection also improves the function of the GSH-Px-GSH system, which manifests itself in the prevention of ROS-dependent lipid peroxidation [ 65 , 66 ]. Consequently, in our studies, we show that topical application of CBD reduces lipid peroxidation, which is revealed by the decreased levels of 8-iso-PGF 2α and 4-HNE in the liver of rats exposed to UVA radiation.…”
Section: Discussionmentioning
confidence: 99%